Movers & fakers - Harrison, Lisi (Harrison, Lisi., 2010)
Skye Hamilton is invited to attend the ultra-exclusive Alphas-only boarding school, where she finds that anyone who is deemed a loser is subjected to humiliation and torment by their classmates and fears that she will soon become the target of their ridicule.